A new collagen solution with high concentration and collagen native structure perfectly preserved. Issue 106 (14th October 2015) - Qi, Pengwei; Zhou, Yuanyuan; Wang, Dalu; He, Zhanhang; Li, Zhongjun
Abstract : Optical photograph of collagen solutions in different solvents. Abstract : Collagen, the most abundant protein in mammals, is widely used for making biomaterials. Usually, organic solvents, such as 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol (HFIP), or acids (H3 PO4, HAc) have been used to disperse collagen to make collagen-based biomaterials. However, the native structure of collagen is often seriously damaged and the concentration of collagen in solution was always relatively low, which greatly limited its application. In this work, we have firstly made a detailed study of the effect of H + and HAc on collagen dispersal in terms of Zeta potential, particle size and Circular Dichroism (CD), followed by using a benign sodium acetate/acetic acid buffer solution, which is proposed to disperse the collagen. The results showed that the collagen solution from a NaAc/HAc buffer solution at pH = 3.0 had both high concentration (100 mg mL −1 ) and perfect native structure preservation (up to 94%). We demonstrated that it was the constant concentration of free H + in the NaAc/HAc buffer solution whose pH was fixed at 3.0 that can maintain an unchanged amount of surface charge on the collagen colloidal particles, which enables the collagen to be dispersed well even at high dose. As an application, the collagen solution from the NaAc/HAc solution at pH 3.0 was successfully electrospun into nanofibers, and the obtained collagen nanofibers can still maintain as much as 57% of its native structure. This study indicated that the novel buffer solution of NaAc/HAc at pH 3.0 could be commonly used in the processing of collagen for a variety of biomaterials based on collagen solutions, and has great potential for use in tissue engineering.